EMPLOYEE STOCK OWNERSHIP PROGRAM (ESOP) DAN NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VERIABEL INTERVENING - Anugraini, Mardiyah; Khusnah, Hidayatul (Universitas Nahdlatul Ulama Surabaya, 2020)
This study aims to investigate the effect of the employee stock ownership program (ESOP) on profitability and firm value. In addition, this study also aims to see the mediating effect of profitability on the effect of ESOP on firm value. This research was conducted on manufactures listed on the Indonesia Stock Exchange (BEI) during 2015-2019. The data analysis technique in this study used the PLS (Partial Least Square) method. The results of this study indicate that the results of this study indicate that profitability partially mediates the effect of ESOP on firm value. This study also found that ESOP has a positive effect on profitability and firm value. This study also found the same thing for the effect of profitability on firm value.